Transgender and gender diverse individuals embodying endometriosis: a systematic review - Giacomozzi, Maddalena; Bouwens, Jip; Aubin, Stéphane Guy; Pastoor, Hester; Verdonk, Petra; Nap, Annemiek (Frontiers in Medicine, 2024)
Transgender and gender diverse (TGD) people embody social and health inequalities that disproportionately affect this community more than the cisgender population. Endometriosis is a chronic condition of the reproductive tract that affects 5-10% of cisgender women. A recent systematic review with meta-analysis uncovered a pooled prevalence of 25.14% among TGD individuals undergoing gender-affirming surgeries. This study aims to investigate the causes of the gap in prevalence of endometriosis between the TGD community and the cisgender population. A systematic search with a fit-for-framework analysis has been conducted. Studies published between 2001 and 2022 in the English language were identified on the PubMed, Web of Science, Sociological abstracts, and PsycInfo databases. 28 peer-reviewed sources were selected. Results were analyzed according to the adjusted developmental framework for embodiment with an intersectional approach. Sources were categorized in multi-levels relating to the identified mechanisms of expression, shaping, interaction and incorporation. The higher prevalence of endometriosis among TGD people compared to the cisgender population reflects a complex phenomenon whereby individual biomedical characteristics, and psychological and environmental factors interplay on multiple levels throughout one's lifespan. Exogenous testosterone as gender-affirming therapy shape TGD bodily characteristics and results in amenorrhea in 80% of cases. However, endometrium and follicular activities are still reported upon testosterone use suggesting endometriosis may be active. It is hypothesized that testosterone use could lead to a hyper-estrogenic state that would stimulate endometriosis proliferation. Additionally, TGD people express lifestyle and environmental factors correlated with endometriosis more often than cisgender women, a.o. history of trauma, low self-image, obesity. Endometriosis interacts with one's quality of life, and especially with gendered expectations related to menstruations, family planning and sexuality. This interference can result in biographical disruption and gender self-perception changes in both cisgender and TGD people.